The Development of Philosophy in Education - Norma Yulianti; Faizin Faizin; Haris Abdillah (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2023)
Philosophy plays a very important role in human thought, as it deals with deeper matters—specifically, the study of knowledge itself. This shows that philosophy is the foundation of all science and knowledge. Philosophers study how humans come to know and how they use knowledge. Since thinking and knowing are two distinct things, philosophy—or the thinking about knowledge—is essential. What are the characteristics of human beings? What do we know about the process? Thinking is done in order to produce knowledge. Knowledge is information that enters a person’s heart after it has been acted upon, combined with understanding and the potential for action. Furthermore, knowledge has the capacity to predict and produce outcomes that reveal patterns. As a result, the effort to develop individuals through education and training—whether personal or in groups—depends greatly on knowledge.